Charging communication networks : from theory to practice - Songhurst, D. J. (Elsevier, 1999)
This book proposes that usage-based charging schemes are essential to generate the incentives necessary for efficient operation of multiservice networks. The rapid development of network technology is enabling sophisticated new services and applications which demand new charging models. The same technology provides the means to operate the right charging schemes. Some of the work done in the European collaborative project CA & dollar;hMAN (Charging and Accounting Schemes in Multiservice ATM Networks). This project combined performance and economic models of network resource usage and cutomer utility to construct simple but effective charging schemes which were implemented and trialled in an advanced management platform.